APPLICATION FOR COUNTING INTENSITY OF EVENTS THROUGH POINT PROCESS CASE STUDY : TECTONIC EARTHQUAKE - Syukri Nugroho, Fazar
Tectonic earthquake is a disaster that really often happens, especially in Indonesia. Definition from BMKG, tectonic earthquake happens because there is sufficient stored elastic strain energy from the earth, the energy is releasing because of the movement from tectonic plates. Research for predicting earthqyake that happens in a certain location is a part of Statistical Seismology. Earthquake prediction cannot exactly predict the components of earthquake, but it should provide the probability with uncertainty of an earthquake's location, time and magnitude. For this purpose, a stochastic point process is needed and the useful concept is point process. The location of earthquake is a realisation of a point process in real world. Beside stochastic model, technology can make the analysis process easier and faster, and can detect a deep information from the earthquake itself. With stochastic model and computing device, models to picture the real process in nature can be build, like a model for intenisty of the earthquake that being followed by a certain distribution.